Fatigue life assessment of a non-load carrying fillet joint considering the effects of a cyclic plasticity and weld bead shape - S. Tsutsumi; K. Morita; R. Fincato; H. Momii (Fracture and Structural Integrity)
Fatigue life depends strongly on irreversible contributions that accumulate during cyclic loading and unloading of structures. However, the correct identification of the loading path in terms of uniaxial or multi-axial stress states, proportional or non-proportional loading is essential because these factors can significantly alter the material response. In this study, finite element analysis was conducted to assess the fatigue crack initiation life of a non-load carrying fillet joint by considering weld bead shape and a cyclic plasticity accumulation during fatigue loading, which is a main cause of crack initiation. Cyclic plasticity behaviour including cyclic hardening and softening together was investigated with an unconventional plasticity model called the subloading surface model and extended to include both elastic boundary and cyclic damage concepts. The cyclic plasticity model can capture realistic plastic strain accumulation during high cycle fatigue under macroscopically elastic stressing conditions